The Bay Psalm book : the first book printed in Bitish North America, 1640 : [the Enigma of the Bay Psalm book] - Haraszti, Zoltan, 1892-1980 (Dover Publications, Incorporated, 2016)
"The Bay Psalm Book was printed just 20 years after the Pilgrims' arrival and remained in use for well over a century. This facsimile of the rare original includes a companion volume, The Enigma of the Bay Psalm Book, which offers an academic study of the Psalter's history and contents. Both books are now presented in a single hardcover volume"--